The political representation of Muslims in Brussels - Fatima Zibouh (Brussels Studies, 2011)
Compared with other major European cities, the Brussels-Capital Region has a unique configuration in terms of the political representation of elected representatives descended from diverse ethnocultural groups, and in particular Muslim elected representatives. Nearly one out of five members of the Parliament of the Brussels-Capital Region is of Muslim origin. This is all the more unique given that, for the first time in Brussels and in the entire European Union, one of the seats in the Brussels Parliament is held by a Muslim member who wears a headscarf (Mahinur Ozdemir). The present article is based on documentary work as well as an empirical approach carried out using interviews which were conducted with Brussels MPs and community stakeholders mobilised before the elections as well as an ethnographic observation of the election campaign. Its objective is to understand the explanatory factors regarding this political representation which is quite unusual in Europe, by formulating the hypothesis of the deciding influence of institutional parameters combined with the demographic evolution and community mobilisation of Muslims in Brussels.